PARTI-A Haptic Virtual Reality Control Station for Model-Mediated Robotic Applications - Elsner, Jean; Reinerth, Gerhard; Figueredo, Luis; Naceri, Abdeldjallil; Walter, Ulrich; Haddadin, Sami (Frontiers in Virtual Reality, 2022)
In this paper, we introduce a tele-robotic station called “PARTI” that leverages state-of-the-art robotics and virtual reality technology to enable immersive haptic interaction with simulated and remote environments through robotic avatars. Our hardware-in-the-loop framework integrates accurate multibody system dynamics and frictional contacts with digital twins of our robots in a virtual environment with real-time computational capabilities. This model mediated hardware-in-the-loop approach to robotic control allows a teleoperator to use the PARTI system to teach, evaluate, and control various robotic applications. In the current contribution, we focus on the general system description, integrated simulation and control framework, and a series of experiments highlighting the advantages of our approach.